The first checklist of the tribe Olethreutini (Lepidoptera: Tortricidae: Olethreutinae) of Thailand - Muadsub, Sopita; Pinkaew, Nantasak (Zootaxa, 2023)
Olethreutini fauna in Thailand consists of 171 species belonging to 57 genera. This checklist is based on literature in which Olethreutini species have been described or recorded and identified specimens that were deposited in Kasetsart Kamphaengsaen Insect Collection (KKIC), Thailand. Of those, 36 species still were reported only in Thailand. Five genera (Lipsotelus, Meiligma, Metrioglypha, Prophaecasia, and Psilacantha) are new records for Thailand. Furthermore, 29 species are also recorded from Thailand for the first time.